Synchrotron FTIR Microspectroscopy Study of the Striatum in 6-Hydroxydopamine Rat Model of Parkinson's Disease. Issue 4 (13th June 2012) - Hongyan Hongyan, Zhu Zhu; Xiao Xiao, Pei Pei; Lingyan Lingyan, Wu Wu; Bo Bo, Liu Liu; Zeming Zeming, Qi Qi; Yuyin Yuyin, Wang Wang
Abstract : In the present study, synchrotron-based Fourier transform-infrared (FTIR) microspectroscopy is used to analyze the biochemical composition of the striatal neurons in normal and Parkinson's disease (PD) rat brain tissues. The rat model of Parkinson's disease is established by destroying the nigrostriatal pathway with 6-hydroxydopamine (6-OHDA). The detailed spectral analyses show the significant changes of cellular compositions such as lipids, and proteins in the striatal neurons of 6-OHDA-lesioned PD rats with respect to control neurons. As a result, the intensities of spectral absorption assigned to lipid of the striatal neurons in PD rats are higher than in control animals. Furthermore, the unsaturation levels of phospholipids decrease in PD neurons with respect to control neurons, indicating a high level of lipid peroxidation. The analysis of protein secondary structure shows the significantly higher ratio ofβ -sheet in PD neurons compared to that of control neurons, suggesting that the abnormal protein structure occurs before their morphological appearances in the striatal neurons. These findings suggest that the biochemical changes in neurons could be involved in the pathogenesis of Parkinson's disease.